Peran Pembimbing dalam Meningkatkan Kecerdasan Spiritual Anak Asuh di Panti Asuhan - Siti Rahma Rambe; Lahmuddin Lubis (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
The purpose of this study was to determine the role of mentors in increasing the spiritual intelligence of adolescents at the Al-Arif Alwashliyah Labuhanbatu orphanage. The focus of this research is how the role of mentors in improving the spiritual intelligence of foster children as the fulfillment of rights and obligations to foster children for their survival and as a supporter of the personality development of adolescents in getting even better spiritual intelligence from the orphanage adviser. Sources of data taken were directly from the head of the orphanage as the leader of the Al-Arif Alwashliyah Labuhanbatu orphanage, and from other informants, namely from the orphanage administrators and from orphanage youth. The data analysis technique used in this study is descriptive qualitative data analysis which involves describing events that occurred in the field. This approach includes data collection, data reduction, data presentation, and drawing conclusions. As with the results of research on the role of mentors in increasing the spiritual intelligence of foster children at the Al-Arif Alwashliyah Labuhanbatu orphanage which is very good where the application, increasing spiritual intelligence is clearly visible from the daily life of orphanage orphans.